2009
DOI: 10.1534/genetics.109.105841
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Value and Fluctuating Selection in an Age-Structured Population

Abstract: Fluctuations in age structure caused by environmental stochasticity create autocorrelation and transient fluctuations in both population size and allele frequency, which complicate demographic and evolutionary analyses. Following a suggestion of Fisher, we show that weighting individuals of different age by their reproductive value serves as a filter, removing temporal autocorrelation in population demography and evolution due to stochastic age structure. Assuming weak selection, random mating, and a stationar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 48 publications
0
25
0
Order By: Relevance
“…Fisher claimed in calculating gene frequencies and selection that individuals should be weighted by their reproductive value. Engen et al (2009b) showed how reproductive value weighting filters out transient stochastic fluctuations in allele frequencies generated by fluctuations in the age structure around the stable age distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Fisher claimed in calculating gene frequencies and selection that individuals should be weighted by their reproductive value. Engen et al (2009b) showed how reproductive value weighting filters out transient stochastic fluctuations in allele frequencies generated by fluctuations in the age structure around the stable age distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Further analysis carried out on the data set after removing this population failed to find any substructure (data not shown). Temporal variations of allelic frequencies in small pelagic fish may result from fluctuations in the dominant age classes in the stock (Mariani et al 2005;Engen et al 2009). Although the samples analysed were not aged, it was possible to retrieve data on size distributions, which can roughly be used as a proxy for the age range.…”
Section: Resultsmentioning
confidence: 99%
“…For a complete census N e = N /σ 2 d is the effective population size (Engen et al 2005b), whereas for a sample we may call it the effective sample size determining the uncertainty in the estimated selection differentials including the effect of the genetic drift.…”
Section: Appendix B: Genetic Drift and Estimation Uncertaintymentioning
confidence: 99%